2018
DOI: 10.1590/1980-5373-mr-2018-0121
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of β´(Cu4Ti) Precipitation During Isothermal Aging of a Cu-4wt.%Ti Alloy

Abstract: This work analyzed experimental and numerically the growth kinetics of β´precipitation of a Cu4wt.%Ti alloy after aging at 400, 500 and 600 °C for times from 0.0166 h to 200 h. Results indicated that the precipitation process is almost controlled by nucleation and growth during aging at 400 °C, originating a slow growth kinetics of precipitation. In contrast, the coarsening of precipitates dominates the precipitation process during aging at 500 and 600 °C. The interfacial energy of interface between the a matr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…With an increase in the titanium content above equiatomic one relative to graphite, the lines from titanium oxides disappear in X-ray diffraction patterns from anode deposits of materials under study, but traces of the presence of a stable β -phase (Cu 3 Ti) appear in the form of a weak line with an interplanar distance of 0.199 nm, which correlates with the data of X-ray phase analysis alloy Cu-4 wt% Ti after aging [7]. According to the authors [6][7][8][9][10], this phase is formed along grain junction lines as a result of cellular or intermittent aging of a supersaturated solid solution of titanium in copper. Atomic force microscopy studies using the Next NT-MTD scanning probe microscope showed that during the reactionary mechanical alloying of copper powder with titanium and carbon, highly fragmented matrix grains with sizes of 200 nm and less are formed in materials under study (Fig.…”
Section: Structure and Phase Compositionmentioning
confidence: 52%
See 2 more Smart Citations
“…With an increase in the titanium content above equiatomic one relative to graphite, the lines from titanium oxides disappear in X-ray diffraction patterns from anode deposits of materials under study, but traces of the presence of a stable β -phase (Cu 3 Ti) appear in the form of a weak line with an interplanar distance of 0.199 nm, which correlates with the data of X-ray phase analysis alloy Cu-4 wt% Ti after aging [7]. According to the authors [6][7][8][9][10], this phase is formed along grain junction lines as a result of cellular or intermittent aging of a supersaturated solid solution of titanium in copper. Atomic force microscopy studies using the Next NT-MTD scanning probe microscope showed that during the reactionary mechanical alloying of copper powder with titanium and carbon, highly fragmented matrix grains with sizes of 200 nm and less are formed in materials under study (Fig.…”
Section: Structure and Phase Compositionmentioning
confidence: 52%
“…An effective increase in the strength and electrical conductivity of Cu-Ti alloys is observed as a result of quench hardening in water from 800 ... 950 ° C for 1...10 h and subsequent aging at 450 °C for 1 h or more due to the precipitation of dispersed particles of the strengthening phase Cu 4 Ti or Cu 3 Ti [6][7][8][9]. The processes of supersaturated solid solution decomposition depending on temperature and time have been studied quite deeply in a number of works [6][7][8][9][10]. However, with an increase in the aging temperature above 500 о С, Cu-Ti alloys rapidly soften due to the processes of coagulation of dispersion particles of the strengthening phase Cu 4 Ti [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical composition of alloys and temperature are usually specified to simulate with Calphad. Additionally, Precipitation/ Kinetics software 18,20,21 was employed to simulate the β´ precipitation in the ferritic α phase matrix. It was considered the bulk nucleation of cuboid β´ precipitates in the ferritic matrix and taking into account the effect of the elastic strain in the matrix.…”
Section: Numerical Methodologymentioning
confidence: 99%
“…The Calphad and Precipitation/Kinetics software has been applied [18][19][20][21][22] successfully to analyze the precipitation process of different multicomponent alloy systems. Calphad permits to obtain the phase stability, interfacial free energy, driving force, coarsening rate constant, Time-Temperature-Precipitation diagrams, growth kinetics of precipitation, size distribution, change of yield strength after aging, etc.…”
Section: Introductionmentioning
confidence: 99%